RSV-Induced Bronchial Epithelial Cell PD-L1 Expression Inhibits CD8(+) T Cell Nonspecific Antiviral Activity - Telcian, Aurica G. (Oxford University Press, 2011)
Respiratory syncytial virus (RSV) is a major cause of bronchiolitis in infants. It is also responsible for high morbidity and mortality in the elderly. Programmed death ligands (PD-Ls) on antigen-presenting cells interact with receptors on T cells to regulate immune responses. The programmed death receptor-ligand 1/programmed death receptor 1 (PD-L1-PD-1) pathway is inhibitory in chronic viral infections, but its role in acute viral infections is unclear. We hypothesized that bronchial epithelial cell (BEC) expression of PD-Ls would inhibit local effector CD8(+) T cell function. We report that RSV infection of primary human BECs strongly induces PD-L1 expression. In a co-culture system of BECs with purified CD8(+) T cells, we demonstrated that RSV-infected BECs increased CD8(+) T cell activation, proliferation, and antiviral function. Blocking PD-L1 on RSV-infected BECs co-cultured with CD8(+) T cells enhanced CD8(+) T cell IFN-γ, IL-2, and granzyme B production. It also decreased the virus load of the BECs. Based on our findings, we believe therapeutic strategies that target the PD-L1-PD-1 pathway might increase antiviral immune responses to RSV and other acute virus infections.